Systematic Literature Review: Religious Moderation in Rejecting Fanaticism in Indonesia - Mochammad Arief Ilyasa (World Journal of Islamic Learning and Teaching, 2025)
This study aims to examine the application of religious moderation in overcoming religious fanaticism in Indonesia, a country with high religious and cultural diversity. The main objective of this study is to understand how religious moderation can reduce the potential for social conflict caused by religious fanaticism. Using a systematic literature review (SLR) methodology, the database used to search for literature is data contained in Google Scholar and the Covidence Application, 6 relevant studies were analyzed using the PICOC-PRISMA criteria. The results of the study indicate that religious moderation can be implemented through inclusive religious education, the role of mass media in disseminating values of tolerance, and government policies that support harmony between religious communities. In addition, factors that influence the emergence of religious fanaticism include narrow understanding of religion, social injustice, and the spread of radical ideology through social media. This study contributes to strengthening multiculturalism and harmony between religious communities in Indonesia.